Investigasi Kejadian Luar Biasa Hepatitis A di Pondok Pesantren X, Jawa Tengah, Indonesia: Bayu Satria Wiratama, Yusrizal, Tutik Inayah Susilaningsih, Akhmad Mukhibin - Bayu Satria Wiratama; Yusrizal Yusrizal; Tutik Inayah Susilaningsih; Akhmad Mukhibin (STIKes Persada Husada Indonesia, 2026)
Research Objective: To describe the epidemiological characteristics, identify risk factors, and recommend control measures for a hepatitis A outbreak at X Islamic Boarding School, Kebumen District, Central Java, Indonesia, in 2022. Methodology: A descriptive study combined with a case-control design was conducted from February 12 to March 17, 2022, involving 1,319 students. A case was defined as a student presenting with symptoms such as fever, fatigue, nausea, vomiting, headache, loss of appetite, abdominal pain, diarrhea, joint pain, and jaundice. Laboratory confirmation was performed using IgM anti-HAV testing. A case-control study with a 1:2 ratio (39 cases and 77 controls) was conducted using purposive sampling. Data were collected through structured interviews to assess demographic characteristics and behavioral risk factors. Bivariate analysis was performed using the chi-square test, and multivariate analysis was conducted using logistic regression. Results: A total of 212 students developed symptoms (attack rate: 16.1%), of whom 45 were laboratory-confirmed cases. The highest attack rates were observed among females (17.5%) and students aged less than 15 years (50.5%). Four behavioral risk factors were significantly associated with infection: not washing hands with soap before eating (OR = 3.26; 95% CI: 1.415–7.541), sharing food from a single container (OR = 3.94; 95% CI: 1.749–8.889), sharing or borrowing eating utensils (OR = 2.96; 95% CI: 1.324–6.648), and frequent snacking (OR = 3.08; 95% CI: 1.293–7.350). Water samples from regular wells and the canteen’s drinking water tested positive for Escherichia coli contamination. The epidemic curve indicated a common-source outbreak pattern. Conclusion: The hepatitis A outbreak was confirmed through epidemiological investigation and laboratory testing. Contaminated water sources and poor hand hygiene practices were identified as the primary transmission routes. The implementation of water treatment, health education, and improved sanitation facilities is essential to prevent future outbreaks in congregate settings.